Tuning electrochemical properties of carbon nanofiber electrodes with selenium heteroatoms for flexible zinc ion capacitors - Wenjie Liu; Fen Qiao; Jikang Zhao (Nano Research Energy)
The N-doping strategy is considered an effective method to regulate the electronic structure of carbon materials and improve their electrochemical performance. However, how to reasonably regulate the types of N-doping species remains a major challenge. Herein, we reported a self-supporting carbon nanofiber electrode codoped with N and Se (N/Se-CNF) for flexible zinc ion capacitor (ZIC). It was found that Se atoms can induce the reduction of Pyrrole-N, which is favorable for Zn ions transfer. Furthermore, ex-situ characterizations and theoretical density functional theory (DFT) calculations have shown that additional Se atoms can provide abundant reaction sites and reduce the adsorption energy of Zn ions. Accordingly, the N/Se-CNF electrode demonstrates impressive rate performance. The N/Se-CNF electrode shows impressive rate performance, retaining 60% capacitance at 20 A·g–1, with an energy density of 95.3 Wh·kg–1 and power density of 160.1 W·kg–1, and a commendable stability cycle, the capacitance retention is 88.1% after 18,000 cycles at a discharge rate of 5 A·g–1. Moreover, a flexible ZIC with N/Se-CNF electrode exhibits a high energy density of 68.8 Wh·kg–1 at 160 W·kg–1. This strategy innovatively regulates N-doping species and offers potential flexible electrodes for advanced energy storage devices.